Analytical Prediction of Optimal Split Ratio for Short-Time Duty PM Brushless DC Motors Considering Winding Thermal Limitation. Issue 4 (4th July 2022) - Li, Quanwu; He, Zili; Jiang, Wei; Liu, Ze; Dong, Wei
ABSTRACT: The temperature gradient of high-torque-density short-time duty permanent magnet (PM) brushless DC motors (BLDCM) is large. Increasing the torque will cause the copper loss and the winding temperature to rise rapidly, which will lead to the risk of the winding insulation damage. A split ratio optimization method is proposed to raise the torque considering winding temperature limitation in this paper. The analytical relationship between the torque, the losses and the split ratio is derived. The transient temperature of the winding is calculated analytically based on the expressions of this analytical relationship. The maximum allowable temperature rise of the winding is converted to the optimization constraint. The optimal split ratio is calculated and the maximum torque within the temperature limit range is obtained. The method is verified by finite element (FE) simulation and experimental test. The FE predicted optimal split ratio value is equal to the analytically predicted value. The error between the simulated and calculated torque is less than 5.7%. The maximum error between measured and analytically predicted temperature is 7.2%. The verification results show that the proposed method can accurately calculate the optimal split ratio and maximizes the torque within the winding temperature limitation.